Mobilidade terena para assentamentos informais urbanos na periferia da cidade: processos de (re)territorialização da Comunidade Indígena do Jardim Inápolis em Campo Grande - MS - Luiz Felipe Barros Lima da Silva (2022)
This paper presentes na analysis of them obility process concerning a Terena indigenous group from the countryside of Mato Grosso do Sul to the peripheries of its capital, Campo Grande, spurring the creation of an informal urban settlement, further entitled as Indigenous Community of Jardim Inápolis. The analysis is based on extensive data collection from Works written about the Terena people in tert wined within formation acquired from field research: both observational practices as well as conversations with their acknowledged leaders. Along side families belonging to the settling, this research aims, through ethnography, to investigate their mobility and urban integration, the progression of the settlement formation and their strategies to adapt to a new environment, which include spacial organization, habitation and social characteristics specific to the Terena. When encompassing all sources of information, it was possible to understand the underlying reasons to their mobility. Never the less, indicators presente throughout the speech of some speakers shed a light on the importance of kinship and companionship to strengthen the group as a whole according to traditional standards.